2021
DOI: 10.1021/acsaem.1c00023
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Lithium Storage in Silica–Tin Composites Enables a Cycle-Stable and High-Capacity Anode for Lithium-Ion Batteries

Abstract: Silica (SiO2) is considered as a promising candidate anode material for next-generation lithium-ion batteries (LIBs) owing to its low cost, abundant reserve on Earth, and relatively high theoretical specific capacity. However, the development of SiO2-based anode materials has been impeded by their poor electrical conductivity and sluggish charge-transfer kinetics. Herein, porous SiO2/tin (SiO2@Sn) composites with tunable SiO2 to Sn molar ratios are fabricated using a scalable, simple, and low-cost ball-milling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 58 publications
(113 reference statements)
0
7
0
Order By: Relevance
“…Despite these desirable features, silica shows a problematic volume change during the cycling process, even though it less than that of elemental silicon . Besides, silica possesses poor electronic conductivity and a relatively low initial Coulombic efficiency (CE) caused by the irreversible formation of lithium silicates and Li 2 O during the initial discharge process on the electrode surface . One effective method for accommodating the SiO 2 volume change and improving its electrical conductivity is to integrate silica with a carbonaceous matrix .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these desirable features, silica shows a problematic volume change during the cycling process, even though it less than that of elemental silicon . Besides, silica possesses poor electronic conductivity and a relatively low initial Coulombic efficiency (CE) caused by the irreversible formation of lithium silicates and Li 2 O during the initial discharge process on the electrode surface . One effective method for accommodating the SiO 2 volume change and improving its electrical conductivity is to integrate silica with a carbonaceous matrix .…”
Section: Introductionmentioning
confidence: 99%
“…10 Besides, silica possesses poor electronic conductivity and a relatively low initial Coulombic efficiency (CE) caused by the irreversible formation of lithium silicates and Li 2 O during the initial discharge process on the electrode surface. 11 One effective method for accommodating the SiO 2 volume change and improving its electrical conductivity is to integrate silica with a carbonaceous matrix. 12 Moreover, it was also observed that the presence of heteroatoms such as nitrogen within carbon/SiO 2 composites can increase the reactivity of the active material, thereby enhancing the capacity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[ 57 ] The Si/SiO 2 @G‐S anode exhibits a significantly smallest R ct among the three electrodes before cycling, suggesting fast charge‐transfer rate between the electrode and electrolyte for Si/SiO 2 @G‐S (Figure 6j). [ 58 ] To further clarify the stable SEI phase, different cycles of EIS of the Si/SiO 2 @G‐S electrode at full delithiation state are obtained in Figure 6k. After 50th and 100th cycle of Si/SiO 2 @G‐S, there is a little change in R ct values.…”
Section: Resultsmentioning
confidence: 99%
“…DLi + ∝ 1/σ 2 , (2) This equation is utilized to determine the diffusion coefficient for the composite before and after cycling [37][38][39][40], and the obtained values for the σ for fresh and for the cell after 70 cycles are 472.2 and 1303.89, respectively, as illustrated in Figure 5b.…”
Section: Resultsmentioning
confidence: 99%